Studies of gallium nitride (GaN) based high electron mobility transistor (HEMTS) - Ong, Eugene Wei Han (Nanyang Technological University, 2024)
GaN (Gallium Nitride) on High Electron Mobility Transistors (HEMTs) has been developed since the early 2000s, however, it is not till recent times that it is commercialised and used for an impressive array of technologically advanced advents. This project delves into the burgeoning field of Gallium Nitride (GaN) based High Electron Mobility Transistors (HEMTs) and their pivotal role in advancing Electric Vehicle (EV) technology. The primary objective is to elucidate the manifold benefits of employing GaNbased HEMTs in EVs, highlighting their transformative impact on efficiency, performance, and sustainability. This is followed by an understanding behind the driving forces of this material, pre and post production, as well as an idea to a real life problem we see today. Through a systematic review and analysis, this study showcases significant strides made in GaN production, underlining its scalability and commercial viability. Moreover, it explores the integration of GaN-based HEMTs into EV inverters, explaining how these components enhance power conversion efficiency and contribute to the overall advancement of electric propulsion systems. Findings reveal a notable surge in GaN production capacity, coupled with widespread adoption in EV applications, particularly in the development of efficient inverters. The study underscores the pivotal role of GaN-based HEMTs in addressing the evolving demands of the automotive industry, where electrification and sustainability are paramount. This study aims to integrate the thermal and electrical properties of GaN into a solution to increase the efficiency in Electric Vehicles in the general process of Transportation Electrification with Singapore’s environmental plan highlighted by the Singapore Green Plan. The solution in this paper targets an effective region of improvement, exploiting a market gap in the development of Electric Vehicles that will yield better results while retaining the aesthetic and functional capability in Electric Vehicles. This thereby provides a multifaceted perspective beginning together financial objectives, government efforts, as well as environmental goals through a potential idea.